Egyptian citrus essential oils recovered from lemon, orange, and mandarin peels: phytochemical and biological value - Ibrahim, Faten Mohamed (2024)
Citrus peels are an important by-product of citrus processing industries, but a large part is considered waste. There has been increased attention in the last five years on these industrial by-products, especially those containing residual essential oils (EOs). Lemon, orange, and mandarin peels from Egypt were subjected to hydro-distillation to obtain EOs, which were analyzed via mass spectrometry (GC/MS) and by building Global Natural Products Social Molecular Networking (GNPS-MN) for the purpose of visually exploring the volatile components of citrus species. The constructed MN revealed that D-Limonene, α-pinene, and β-pinene are the dominant volatile constituents in the three Egyptian citrus species. The EOs from three citrus peels exhibited promising activities as antioxidants using two tested methods: 1,1-diphenyl-2-picryl-hydrazil (DPPH) and nitric oxide (NO) compared with vitamin C. Lemon EO proved excellent antimicrobial activity against Gram-positive and negative bacteria. Additionally, the three citrus EOs showed good activities against the yeast Candida albicans. Regarding the anti-inflammatory assay, the three citrus EOs showed promising activities as COX-1 and COX-2 inhibitors. This study concludes that EOs extracted from citrus peel waste can be valorized as an innovative strategy for food preservation or may be incorporated in cosmetics and pharmaceutical formulations in alignment with circular economy principles.